Adoptive Cell Therapy in Pediatric and Young Adult Solid Tumors: Current Status and Future Directions - Ligon, John A.; Wessel, Kristin M.; Shah, Nirali N.; Glod, John (Frontiers in Immunology, 2022)
Advances from novel adoptive cellular therapies have yet to be fully realized for the treatment of children and young adults with solid tumors. This review discusses the strategies and preliminary results, including T-cell, NK-cell and myeloid cell-based therapies. While each of these approaches have shown some early promise, there remain challenges. These include poor trafficking to the tumor as well as a hostile tumor microenvironment with numerous immunosuppressive mechanisms which result in exhaustion of cellular therapies. We then turn our attention to new strategies proposed to address these challenges including novel clinical trials that are ongoing and in development.